KOMPETENSI PUSTAKAWAN DALAM MENGANALISIS KATA KUNCI - Putri, Rizkiya; Royani, Yupi; Fadhilah, Farah; Sulaiman, Madiareni (BACA: Jurnal Dokumentasi dan Informasi, 2021)
This study aims to determine the frequency of ISJD keyword analysis in the five PDDI LIPI Regional Libraries, compare the frequency of keywords between regions, and the competence in analyzing keywords. This study used qualitative research methods with a population of 27 people. The survey results are based on keyword analysis and questionnaires, broad into three aspects: knowledge, infrastructure, and training. Also, in-depth interviews were conducted with five informants, with specific criteria on length of work and experience in processing library materials. The data collection stage found that most keywords were produced by the Bandung Regional Library (45%), and the top three keywords were identified in each area. In the aspect of knowledge, librarians in each area generally understand DDC, thesaurus, and EYD (55-80%) and science and technology symbols (45-55%). Most librarians who analyze keywords understand the ISJD, LCSH, and other Thesaurus fields. However, the five informants understood at a different stage and prioritized using the thesaurus. In infrastructure aspects, it was found that the internet network was very influential (60%), with sufficient facilities, which was also agreed by the informants. However, there are still obstacles in business processes and ISJD systems (30-41%). In the training aspect, respondents have received it (85%), but need refreshments (59%) and work guidance documents. So, it can be concluded that librarian competence still needs to be improved in journal processing in ISJD.